Beetroot juice improves on-water 500-m time-trial performance and laboratory-based paddling economy in national and international-level kayak athletes - Peeling, P.; Cox, G. R.; Bullock, N.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
We assessed the ingestion of a beetroot juice supplement (BR) on 4-min laboratory-based kayak performance in national level male (n = 6) athletes (Study A), and on 500-m on-water kayak time-trial (TT) performance in international level female (n = 5) athletes (Study B). In Study A, participants completed three laboratory-based sessions on a kayak ergometer, including a 7 × 4 min step test, and two 4 min maximal effort performance trials. Two and a half hours before the warm-up of each 4 min performance trial, athletes received either a 70 ml BR shot containing ~4.8 mmol of nitrate, or a placebo equivalent (BRPLA). The distance covered over the 4 min TT was not different between conditions; however, the average VO2 over the 4 min period was significantly lower in BR (p = .04), resulting in an improved exercise economy (p = .05). In Study B, participants completed two field-based 500 m TTs, separated by 4 days. Two hours before each trial, athletes received either two 70 ml BR shots containing ~9.6 mmol of nitrate, or a placebo equivalent (BRPLA). BR supplementation significantly enhanced TT performance by 1.7% (p = .01). Our results show that in national-level male kayak athletes, commercially available BR shots (70 ml) containing ~4.8 mmol of nitrate improved exercise economy during laboratory-based tasks predominantly reliant on the aerobic energy system. Furthermore, greater volumes of BR (140 ml; ~9.6 mmol nitrate) provided to international-level female kayak athletes resulted in enhancements to TT performance in the field.